2021
DOI: 10.1111/1556-4029.14687
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Safer at Home order on the frequency of DUI breath alcohol tests in Los Angeles County

Abstract: The current data from The National Center for Statistics and Analysis (NCSA) Fatality Analysis Reporting System (FARS) shows that, in Los Angeles County, 670 deaths were involved in a motor vehicle traffic crash in 2018 [1]. There is evidence that some drivers in California have accepted the practice of drinking and driving [2] even though there is a perceived high risk of arrest [3,4]. This situation may actually be underestimated due to underreporting of actual alcoholimpaired driving [5].Los Angeles County … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the present analysis, we found an increased rate of assaults (44% increase) and overall penetrating trauma (also a 44% increase) in the POST period compared to the PRE period, which coincide with increased firearms sales associated with the COVID-19 pandemic [ 28 – 31 ]. In addition, this study found a 32% increase in motor vehicle collisions, which may be partially explained by other studies finding an increase in risky driving behaviors including driving under the influence of alcohol, speeding, and failure to wear seatbelts in 2020, the most recent year for which data is available [ 32 , 33 ]. While this data is concerning, further multicenter studies are needed to confirm the generalizability of these trends and attempt to elucidate if there are any opportunities for primary prevention to curtail these concerning findings.…”
Section: Discussionmentioning
confidence: 56%
“…In the present analysis, we found an increased rate of assaults (44% increase) and overall penetrating trauma (also a 44% increase) in the POST period compared to the PRE period, which coincide with increased firearms sales associated with the COVID-19 pandemic [ 28 – 31 ]. In addition, this study found a 32% increase in motor vehicle collisions, which may be partially explained by other studies finding an increase in risky driving behaviors including driving under the influence of alcohol, speeding, and failure to wear seatbelts in 2020, the most recent year for which data is available [ 32 , 33 ]. While this data is concerning, further multicenter studies are needed to confirm the generalizability of these trends and attempt to elucidate if there are any opportunities for primary prevention to curtail these concerning findings.…”
Section: Discussionmentioning
confidence: 56%
“…Our study has shown that, overall, during the COVID-19 lockdown, the number of traffic tests was much smaller (5.29 v 8.52 cases/day), as found by other studies. For example, Apodaca et al found a more than 40% decrease in March and April 2020 compared to the same months from 2019 in the number of blood alcohol tests performed in Los Angeles County [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have shown that the restrictions generated by the COVID-19 pandemic shifted the pattern of BrAC results in drivers. For example, Apodaca et al showed a significant decrease in the number of driving under the influence (DUI) BrAC tests performed in Los Angeles County in March-April 2020 versus 2019, associated with a substantial reduction in the number of DUI-related traffic accidents [10] . Beccegato et al, on the other side, suggested, using a case-control study, that chronic excessive alcohol and illicit substance abuse were more frequent during the COVID-19 lockdown [11] .…”
Section: Introductionmentioning
confidence: 99%